Parâmetros biológicos e morfológicos de duas espécies de morcegos do gênero Artibeus (Chiroptera:Phyllostomidae) - Vasconcelos, Rumenigg Barboza de (2014)
The aim of this study was to compare the body measurements of two species of frugivore bats (Artibeus planirostris and Artibeus cinereus) that co-occur in the Biological Reserve Guaribas, State of Paraiba, Brazil. A total of 118 individuals collected in mist net between June and October 2013 were analyzed. Body mass, wingspan, the length of the wing bones and tibia of 65 A. planirostris and 53 A. cinereus were measured. The two species showed sexual dimorphism in size, with females significantly larger than males. Regressions (SMA) between morphometric variables for both species tend to differ significantly from isometry, indicating that there were differences in form between these two species, a result confirmed by discriminant analysis. Wing measures tended to grow less than expected in relation to body mass, which may be an adaptation to reduce drag and allow higher speeds flying in larger individuals. Furthermore, there was a positive correlation between body mass and aspect ratio, which suggests a tendency to narrowing of the wings in larger individuals (another adaptation that allows faster flight). Unlike the wing, the tibia in both species increased in size more than expected with increased body mass. This process may be related to increased investment in the tibia in order to support the increasing weight gain in larger bats.